2020
DOI: 10.1111/ijfs.14862
|View full text |Cite
|
Sign up to set email alerts
|

Understanding cassava varietal preferences through pairwise ranking of gari‐eba and fufu prepared by local farmer–processors

Abstract: Within communities in Osun and Imo States of Nigeria, farmer–processors grew and processed a diverse set of improved and landrace cassava varieties into the locally popular foods, gari, eba and fufu. Local and 15 main varieties were grown in a ‘mother and baby trials’ design in each state. Mother trials with three replications were processed by farmer–processors renown in their community for their processing skills. Baby trials were managed and processed by other farmer–processors. The objective was to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 38 publications
(97 citation statements)
references
References 45 publications
11
86
0
Order By: Relevance
“…The “soaked gari” was prepared as described by Teeken et al ( 37 ). The panelists were presented with 5 g of gari, 2.5 g of sugar, and 10 mL of cold water to use to prepare as they would on their own.…”
Section: Methodsmentioning
confidence: 99%
“…The “soaked gari” was prepared as described by Teeken et al ( 37 ). The panelists were presented with 5 g of gari, 2.5 g of sugar, and 10 mL of cold water to use to prepare as they would on their own.…”
Section: Methodsmentioning
confidence: 99%
“…Following a consultation with RTB experts from different backgrounds and disciplines, 11 food products particularly important for RTB‐based staple diets in SSA were selected for the research reported in this issue. Multidisciplinary teams of breeders, social scientists, food technologists and others used new methods for capturing user quality preferences (Forsythe et al ., 2021; Teeken et al ., 2021), through surveys and product evaluations conducted with farmers, traders, processors and consumers. It is notable that the Forsythe et al .…”
Section: Figurementioning
confidence: 99%
“…fr) is an ambitious initiative to elucidate basic information regarding root quality traits. Several research articles regarding root quality traits and post-harvest processing have recently been published (Alamu et al 2021;Bechoff et al 2018;Dufour et al 2021;Escobar et al 2021;Goddard et al 2015;Iragaba et al 2021;Luna et al 2021;Ndjouenkeu et al 2021;Teeken et al 2018Teeken et al , 2021Thiele et al 2021;Tran et al 2021). The availability of this critical knowledge and reliable high-throughput phenotyping protocols will improve the efficiency of breeding for root quality traits.…”
Section: Understanding and Dissecting Quality Traits For Human Consumptionmentioning
confidence: 99%